Redaksi dan Daftar Isi, Jurnal Arsitekta Vol. 03 No. 01, Mei 2021 - ojsadmin TAU (Arsitekta : Jurnal Arsitektur dan Kota Berkelanjutan, 2021)
Redaksi dan Daftar Isi, Jurnal Arsitekta Vol. 03 No. 01, Mei 2021